the role of Green Human Resources Management Practices in strengthening the Strategic Positioning An Analytical Research on Leaders opinion in the Nongovernmental Hospitals in Erbil - M. Ebabekir, Kosret (Journal of Economics and Administrative Sciences, 2021)
This research is seeks to state the role of Green Human Resources Management Practices and their dimensions (Green Employment and Selection, Green Performance Assessment, Green Training & Development and Green Compensation and Stimulation Systems) in strengthening the Strategic Positioning in the Nongovernmental Hospitals in Erbil city, and aims to analyze the relationship between Green Human Resources Management Practices and Strategic Positioning and to show the impact of Green Human Resources Management Practices in determining the Strategic Position.            It is depended on a questionnaire as key tools for achieving data, as designed on some hypotheses. The questionnaire dividend on (50) people who work in the researched Hospitals which they have the manager, department and unit officer, tested the relationship and impact between research variables for achieving the answers of the research problem by using a group of statistical tools in (SPSS) program.The research has reached a set of conclusions, the most important of which is the correlation and impact of Green Human Resources Management Practices in enhancing Strategic Positioning. The research recommends the need for more attention to environmental implications in human resources management practices and to focus on training and developing their green practices while building an integrated knowledge of strategic positioning